2017
DOI: 10.1016/j.ajpath.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A Role for cAMP and Protein Kinase A in Experimental Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a devastating intestinal disease that has been associated with Cronobacter sakazakii and typically affects premature infants. Although NEC has been actively investigated, little is known about the mechanisms underlying the pathophysiology of epithelial injury and intestinal barrier damage. Cyclic adenosine monophosphate (cAMP) and protein kinase A (PKA) are important mediators and regulators of apoptosis. To test the hypothesis that C. sakazakii increases cAMP and PKA activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…In our study, salmeterol may also have induced cyclic adenosine monophosphate (cAMP), the typical intracellular second messenger of β2ARs. Previously, the cAMP/protein kinase A (PKA) pathway was reported to promote apoptosis in NEC [38]. Whether both G-protein-biased (β2ARs/cAMP/PKA) and β-arrestin-2-biased (β2ARs/β-arrestin-2/BiP) signaling pathways induce apoptosis may be worthy of future study.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, salmeterol may also have induced cyclic adenosine monophosphate (cAMP), the typical intracellular second messenger of β2ARs. Previously, the cAMP/protein kinase A (PKA) pathway was reported to promote apoptosis in NEC [38]. Whether both G-protein-biased (β2ARs/cAMP/PKA) and β-arrestin-2-biased (β2ARs/β-arrestin-2/BiP) signaling pathways induce apoptosis may be worthy of future study.…”
Section: Discussionmentioning
confidence: 98%
“…correlation on intestinal fatty acid binding protein with timing of ischemia and severity of tissue injury(23)). Currently, the administration of a protein kinase A inhibitor(24) and milk-derived exosomes(25) are being studied in a rat model with promising results as potential treatments for NEC.…”
Section: Modeling Nec In the Ratmentioning
confidence: 99%
“…Although the exact aetiology of IBD is not well known, it is believed that genetic susceptibility, environmental factors, a dysfunctional immune system and changes to the gut microbiota are involved in the onset and progression of this disease [ 33 ]. Different studies have implicated cAMP in inflammatory disorders [ 12 , 24 , 34 ]. Zimmerman et al showed that cAMP dysregulates intestinal epithelial cell restitution through PKA indicating that increased levels of cAMP in intestinal epithelial cells inhibit the migratory and restitutive potential in the gut [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zimmerman et al showed that cAMP dysregulates intestinal epithelial cell restitution through PKA indicating that increased levels of cAMP in intestinal epithelial cells inhibit the migratory and restitutive potential in the gut [ 12 ]. Additionally, PKA inhibition appears to protect against gut injury in the rat pup model [ 24 ]. H89 is an isoquinoline derivative that inhibits PKA by acting as competitive antagonists of ATP at its binding site on the PKA catalytic subunit [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation